DESIMINASI DAKWAH Gus BAHA’ DAN ANTUSIASME NETIZEN DI MEDIA SOSIAL - musyaffa musyaffa (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Muhammad Baha'udin Nursalim, Gus Baha' was named the Da'i of The Year 2020. During the Covid19 pandemic, the pattern and study of his da'wah communication also enlivened social media. How does Gus Baha' convey the message of da'wah on social media so that it attracts mad'u's attention? How does Mad'u respond to Gus Baha's da'wah style through social media? The author revealed the question by analyzing it through a qualitative approach and descriptive method. The author collects several data and fact findings from Instagram, Youtube, and Facebook which officially and authentically package their da'wah. The results of the study show that: First, Gus Baha' in preaching tends to be humorous, full of 'jokes' but full of Islamic scientific treasures. Comprehensive da'wah message with logic and scientific argumentation. He is Hafidz as well as mufassirin, making Gus Baha 'more flexible in conveying messages. Second, netizens or mad'u responded to Gus Baha's study with positive comments. Although, some mad'u often repeat the content in order to understand.